ANALISIS PERENCANAAN PERSEDIAAN BAHAN BAKU PADA PT. PESONA ARNOS BETON DI KEDAMEAN, GRESIK - Muhammad Ade Reza Kurniawan; Zainal Arief (Jurnal Intent: Jurnal Industri dan Teknologi Terpadu, 2023)
This study aims to evaluate the planning of material requirements at PT Pesona Arnos Beton which is located at Jl. Raya Kedamean, Banyuurip Village, Kedamean District, Gresik Regency. The company is engaged in the manufacturing industry of concrete and paving products. Examples of goods produced are Paving, Kanstin, TU, U-ditch, and Box Culvert. Continuous Review System (Q system) is an alternative solution to overcome the problems that exist at PT Pesona Arnos Beton. Data collection methods such as material demand and inventory data are carried out using interview techniques and direct observation. Forecasting is done to forecast the need for raw materials in the next period using Minitab software with the Single Exponential Smoothing and Moving Average methods. Then the calculation is carried out on the data that has been obtained using the Continuous Review System method (Q system) which results in an effective material requirement planning arrangement for the future. PT Pesona Arnos Beton using Minitab 20 software is carried out with the Moving Average and Single Exponential Smoothing forecasting methods. produces the smallest MAPE, MAD, and MSD values are with Single Exponential Smoothing which from the forecasting results obtained the total demand for raw materials for paving and concrete products. The calculation results show that the Q system (continuous review system) produces a minimum total cost. the total inventory cost of cement raw materials is more efficient Rp. 108,039,529, stone ash raw materials save Rp.447,747,948, lumajang sand raw materials save Rp.220,346,921, coral saves Rp.66,527,830, iron 6 saves Rp.21,338,002, and iron 8 saves Rp.29,672,213.